Public policies in higher education for the indigenous peoples of the state of Paraná, Brazil: trajectories, challenges and perspectives (Práxis Educativa, 2013)
The experience on the admittance and permanence of indigenous students in public higher education institutions which are the promoters of public policy in higher education in the state of Paraná, Brazil, is provided. Current article is based on the indigenous students’ trajectories at the state universities of Paraná when they were admitted through the Indigenous Entrance Exam. In fact, their permanence in higher education institutions has been possible due to the dual belonging of schooling and ethnicity. It highlights the limits of the State’s role in this policy since their permanence requires higher education policies actually aimed at these subjects and sensitive to the traits built by them. Current analysis is the product of a review of the literature, document analysis and content analysis of interviews with indigenous students and recently graduated indigenous professionals. The uniqueness of the experience in the state of Paraná in the last decade is acknowledged. In fact, its consolidation has been foregrounded on the effective action by the above-mentioned state, by government-run universities and by indigenous leaders and communities. Keywords: Higher Education. Affirmative actions. Indigenous peoples.